The thickness of heel fat-pad in patients with plantar fasciitis - Belhan, Oktay; Kaya, Mehmet; Gurger, Murat (Turkish Assoc Orthopaedics Traumatology, 2019)
Objective: The aim of this study was to investigate the thickness of heel fat pad (THP) and to detect the relationship between the plantar fasciitis (PF) and age, occupation, BMI, longitudinal arch, the thickness of heel fat-pad in the patients with PF. Methods: A total of 50 patients (29 women and 21 men; mean age: 46.5 years (range: 22-70)) that were diagnosed with PF were included to this study. Patients' affected side were compared with the healthy opposite side with the angle of medial arch (AMA) and first metatarsophalangeal angle (FMTPA) on the foot radiograms, and THP and thickness of first metatarsal fat pad (TFMFP) using ultrasonography (USG) of both feet. Results: The mean AMAs of feet with pain and without pain were 122.56 degrees and 120.60 degrees, respectively. The mean FMTPAs of feet with pain and without pain were 14.72 degrees and 14.40 degrees, respectively. The mean THPs of feet with pain at the point of the medial calcaneal tubercle and the mean TFMFPs of the feet with pain at the point of the first metatarsal head were 19.45 mm and 6.75 mm, respectively. The mean THPs of feet without pain at the point of the medial calcaneal tubercle and the mean TFMFPs of the feet without pain at the point of the first metatarsal head were 19.94 mm and 6.75 mm, respectively. It was observed that the mean AMA in the heels with pain was significantly higher than that of the heel without pain (p < 0.05) and the mean THP in the heels with pain was significantly thinner than that of the heel without pain (p < 0.05). Conclusion: The results indicate that USG is an accurate and reliable imaging technique for the measurement of THP in the diagnosis of plantar fasciitis and the heel pad was thinner in the painful heels of patients with plantar fasciitis. (C) 2019 Turkish Association of Orthopaedics and Traumatology. Publishing services by Elsevier B.V.
Keywords: Plantar fasciitis; Heel fat-pad; Ultrasonography; Angle of medial arch; Heel pain